The Role of Digital Technology in the Development of Sharia Entrepreneurship in Community Empowerment Efforts - Rudila Rudila Wati; Evan Stiawan; Andi Harpepen (Borneo Islamic Finance and Economics Journal, 2026)
Abstract This research aims to understand the role of digital technology in supporting the development of sharia entrepreneurship and its contribution to community empowerment in the Perumdam Area, Bengkulu City. The research uses a qualitative method with data collection techniques through observation, interviews, and documentation from five research informants. The results of the study show that digital technology plays an important role as a means of business communication, promotional media, expanding market reach, and building good relationships with consumers, while still paying attention to sharia principles in it. In addition, it contributes to community empowerment through increasing family economic income, creating job opportunities, and community participation in economic activities, so that community business independence is formed. The novelty of this research lies in its focus on the integration of digital technology and sharia entrepreneurship practices at the micro level and their direct implications for community empowerment. Unlike previous studies that generally discuss digitalization, entrepreneurship training, or Islamic economics separately, this study provides a comprehensive perspective by examining how the utilization of digital technology in sharia-based MSMEs contributes to improving economic welfare, creating employment opportunities, and strengthening community independence in the Perumdam Area of Bengkulu City. Keywords: Digital Technology, Sharia Entrepreneurship, Community Empowerment